Evaluation of the Effects of Diode (980 Nm) Laser on Gingival Inflammation after Nonsurgical Periodontal Therapy - Zare, Davoud; Haerian, Ahmad; Molla, Reza; Vaziri, Farzane (Journal of Lasers in Medical Sciences, 2013)
Introduction: Periodontitis is an inflammatory disease, for which, scaling and root planning (SRP) is the common approach for non-surgical control of inflammation. Using lasers is another approach in the first phase of periodontal treatment for control of inflammation. Diode laser has some beneficial effects such as acceleration of wound healing, promotion of angiogenesis and augmentation of growth factor release. Thus the aim of this study is the evaluation of diode laser (980 nm) effect on gingival inflammation when it is used between the first and second phase of periodontal treatment, in comparison with common treatment (SRP) modality alone. Methods: In this study, 21 patients with moderate to severe chronic periodontitis were selected and divided in to control group (SRP) and test group (SRP + laser). Two months after the last scaling and laser radiation, indexes including gingival level (GL), bleeding on probing (BOP) and modified gingival index (MGI) were recorded and compared with baseline. Results: Two months after the beginning of the study, all indices improved in both groups. The indices were not different between two groups except for BOP which was lower in laser group. Conclusion: Based on overall improvement in parameters such as superiority of laser application in some indices, lack of thermal damage and gingival recession with the specific settings used in this study, the application of laser as an adjunctive treatment together with common methods is preferable.